Имитационное моделирование процесса вертикального зондирования гидрофизических полей водной среды - Савкова, Е. О. (НТУ "ХПИ", 2010)
Разработаны классы объектов, образующих структуру информационной системы мониторинга гидрофизических полей водной среды. Описание классов включает параметры объектов, влияющие на состав и функционирование системы, и методы, определяющие действия с экземплярами классов. Предложены дополнительные управляющие классы для описания взаимодействия объектов и имитации процесса зондирования.

The classes of objects which form the structure of the informative system of monitoring of the hydrophysical fields of water environment are developed. Description of classes includes the parameters of objects, which influence on composition and functioning of the system, and methods which determine an action with the copies of classes. Additional managing classes are offered for description of cooperation of objects imitations of sounding process.
Imitating simulation of the aquatic environment hydrophysical fields vertical sounding process
Keywords: мониторинг природных сред; гидрофизический эксперимент; гидрофизические системы; информационная система мониторинга; объектно-эволюционная модель; monitoring; hydrophysical fields; water environment; informative system of monitoring